2021
DOI: 10.1039/d1se00652e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient utilization of crude bio-oil: the synthesis of nitrogen-doped hierarchically porous carbon as electrocatalysts for the oxygen reduction reaction

Abstract: Bio-oil, the unavoidable liquid product of the thermal conversion of biomass, shows high carbon content and aromatic compounds to be a promising carbon precursor. Herein, nitrogen-doped hierarchically porous carbons (NHPCs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The nature of carbon precursors is crucial to the physicochemical characteristics of porous carbons. However, one single type of precursor seems to be insufficient to balance the porous structure and electrical conductivity. Generally, biomass-derived porous carbons are easy to obtain the hierarchically porous structure as most biomass possesses natural pores with broad pore size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of carbon precursors is crucial to the physicochemical characteristics of porous carbons. However, one single type of precursor seems to be insufficient to balance the porous structure and electrical conductivity. Generally, biomass-derived porous carbons are easy to obtain the hierarchically porous structure as most biomass possesses natural pores with broad pore size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 69 synthesized N-doped hierarchically porous carbons by pyrolysis from bio-oil (N-oil) as the carbon and nitrogen source and zinc chloride as the activating agent and template. The N-oil was produced from the pyrolysis of a mixture of pine and polyamide.…”
Section: Resultsmentioning
confidence: 99%
“…[70][71][72][73] At low proportions of zinc, microporous materials are obtained, while at high proportion structures, mesoporosity and macroporosity are observed, suggesting the collapse of microporous structures during the activation process. 30,69 Shang et al 73 reported that the use of ZnCl 2 as an activating agent exerts a strong dehydration effect, which significantly reduces the overall carbonization temperature, suppresses tar formation and results in the formation of open micro and mesopores in the structure. Activation with a low amount of ZnCl 2 produces more micropores due to slight dehydration of the carbon surface, while the use of large amounts of ZnCl 2 gives a much stronger dehydration effect that causes increased pores, stemming from a greater mesoporous character.…”
Section: Resultsmentioning
confidence: 99%
“…This excellent catalytic performance can be attributed to the availability of basic sites and the formation of highly dispersed metal Pt nanoparticles with uniform and small size ( d = 1–2.5 nm) due to the high specific surface area of the carbon carrier. Compared to other solid biomass carbon sources, biotar is a soft carbon precursor with good thermoplasticity . This unique property allows active agents and metals to be mixed with biotar at the molecular level to achieve uniform doping and functional modifications during the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other solid biomass carbon sources, biotar is a soft carbon precursor with good thermoplasticity. 21 This unique property allows active agents and metals to be mixed with biotar at the molecular level to achieve uniform doping and functional modifications during the synthesis process. However, monometallic catalysts often suffer from poor hydrothermal stability and low selectivity and yield of FDCA.…”
Section: Introductionmentioning
confidence: 99%